Etnomatematika: Eksplorasi Geometri pada Tradisi Meron di Sukolilo Kabupaten Pati - Mus’ifah, Iflatul; Azka, Raekha (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Mathematics learning can be realized by collaborating with the culture found in the community. The meron tradition is one of the cultures in Sukolilo Pati with a religious theme aimed at commemorating the birthday of the Prophet Muhammad. This study aims to explore more deeply the geometry of the meron tradition in Sukolilo. The research method used in this study is a qualitative method with an ethnographic approach. This type of research is explorative research. The data analysis techniques used in the research are data reduction, data presentation (data display), and drawing conclusions. The results of the study indicate the existence of ethnomathematics in geometry material which can be reviewed from each part of the meron. In the circular mustaka meron, in the gunungan section there is a curved side space, namely the tube, and in the ancak meron section there are various kinds of geometric shapes such as triangles, persegi, trapezoidal rectangles and rectangular pyramid spaces. Then there are elements of geometry on the top of the ancak such as points, lines, angles, midwives, and space.